Evaluation of Copper-Contaminated Marginal Land for the Cultivation of Vetiver Grass (Chrysopogon zizanioides) as a Lignocellulosic Feedstock and its Impact on Downstream Bioethanol Production - Emily M. Geiger; Dibyendu Sarkar; Rupali Datta (Applied Sciences, 2019)
Metal-contaminated soil could be sustainably used for biofuel feedstock production if the harvested biomass is amenable to bioethanol production. A 60-day greenhouse experiment was performed to evaluate (1) the potential of vetiver grass to phytostabilize soil contaminated with copper (Cu), and (2) the impact of Cu exposure on its lignocellulosic composition and downstream bioethanol production. Dilute acid pretreatment, enzymatic hydrolysis, and fermentation parameters were optimized sequentially for vetiver grass using response surface methodology (RSM). Results indicate that the lignocellulosic composition of vetiver grown on Cu-rich soil was favorably altered with a significant decrease in lignin and increase in hemicellulose and cellulose content. Hydrolysates produced from Cu exposed biomass achieved a significantly greater ethanol yield and volumetric productivity compared to those of the control biomass. Upon pretreatment, the hemicellulosic hydrolysate showed an increase in total sugars per liter by 204.7% of the predicted yield. After fermentation, 110% of the predicted ethanol yield was obtained for the vetiver grown on Cu-contaminated soil. By contrast, for vetiver grown on uncontaminated soil a 62.3% of theoretical ethanol yield was achieved, indicating that vetiver has the potential to serve the dual purpose of phytoremediation and biofuel feedstock generation on contaminated sites.